Visual performance of myopia control soft contact lenses in non-presbyopic myopes - Sha J; Tilia D; Diec J; Fedtke C; Yeotikar N; Jong M; Thomas V; Bakaraju RC (Clinical Optometry, 2018)
Jennifer Sha,1 Daniel Tilia,1,2 Jennie Diec,1 Cathleen Fedtke,1,2 Nisha Yeotikar,1 Monica Jong,1,2 Varghese Thomas,1 Ravi C Bakaraju1,2 1Brien Holden Vision Institute, Sydney, NSW, Australia; 2School of Optometry and Vision Science, University of New South Wales, Sydney, NSW, Australia Purpose: To compare the visual performance of soft contact lenses reported to reduce myopia progression. Methods: In a double-blind, randomized, crossover trial, 30 non-presbyopic myopes wore MiSight™, center-distance Proclear® Multifocal (+2.00 D add), and two prototype lenses for 1 week each. High- and low-contrast visual acuities at 6 m, and 70 and 40 cm; stereopsis at 40 cm; accommodative facility at 33 cm; and horizontal phoria at 3 m and 33 cm were measured after 1 week. Subjective performance was assessed on a numeric rating scale for vision clarity, lack of ghosting, vision stability, haloes, overall vision satisfaction, and ocular comfort. Frequency of eye-strain symptoms and willingness to purchase lenses were also reported with categorical responses. Participants reported wearing times (total and visually acceptable). Linear mixed models and chi-square tests were employed in analysis with level of significance set at 5%. Theoretical optical performance of all lenses was assessed with schematic myopic model eyes (−1.00, −3.00, and −6.00 D) by comparing the slope of the edge spread function (ESF), an indicator for optical performance/resolution and the blur patch size of the line spread function, an indicator for contrast, between the lenses. Results: Proclear Multifocal and MiSight provided the best distance acuities. However, the prototype lenses were rated significantly higher for many subjective variables, and there were no subjective variables where commercial lenses were rated significantly higher than the prototypes. Theoretical optical performance showed steeper slopes of the ESF and greater blur patch sizes of the LSP with commercial lenses, supporting the clinical findings of better visual acuities but reduced subjective performance. Participants wore prototypes longer and reported their vision acceptable for longer each day compared to MiSight. Both prototypes had the highest willingness-to-purchase rate. Conclusions: The prototypes were better tolerated by myopes compared to the commercial soft contact lenses currently used for slowing myopia progression. Keywords: accommodation, theoretical optical performance, extended depth of focus